Study of clinical profile and association of severity with contact sensitivity of hand eczema patients - Hassan, Shahid; Ranjan, Ashutosh (International Journal of Research in Dermatology, 2019)
Background: This present study was to evaluate the clinical profile, severity and its pattern as well as association between contact sensitivity with its severity in hand eczema patients. Methods: A detailed demographic profile, occupation, history regarding onset of disease, duration, progress of hand dermatitis, aggravating and relieving factors, seasonal variations, presence of atopy in self or family, day to day work, hobbies, and past and present treatment were performed to all cases of hand eczema. Severity of hand eczema was assessed by using hand eczema severity index (HECSI). Patch test was applied to all cases with standard Indian patch test battery as approved by contact dermatitis and occupational dermatoses forum of India. Data was applied by using SPSS version 26 software. P value was taken equal to or less than 0.05 for significant differences. Results: Hand eczema was commonly seen in male and middle age group (31-45 years) patients. Masons, house wives and farmers were mostly infected with hand eczema. Hyperkeratotic eczema and wear and tear dermatitis were the most common type of hand eczema. Potassium dichromate and nickel were the most common antigen/allergens. HECSI score 40-60 was seen in majorities of hand eczema cases. And there was no statistical significant association seen in between severity and positive patch test sensitivity in patients with hand eczema. Conclusions: Works associated with exposure to various chemical agents are at higher risk for developing hand eczema. Our study will of immense help to patients for identification of contact sensitizer and prevention from hand eczema.